1998
DOI: 10.1200/jco.1998.16.5.1642
|View full text |Cite
|
Sign up to set email alerts
|

BRCA-associated breast cancer in young women.

Abstract: BABC present with adverse clinical and histopathologic features when compared with cases not associated with BRCA mutations. However, the prognosis of BABC appears to be similar to that of nonassociated cancer. Further studies of incident cases are necessary to define the independent prognostic significance of germline BRCA mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
139
2
8

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(158 citation statements)
references
References 14 publications
8
139
2
8
Order By: Relevance
“…HER2/neu expression was infrequent and did not differ between the BRCA1-related tumours and the controls, which is in line with previous findings (Lynch et al, 1998). In accordance with previous publications concerning E-cadherin expression in BRCA1 carriers (Robson et al, 1998;Armes et al, 1999;Jacquemier et al, 1999), we did not observe different expression levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…HER2/neu expression was infrequent and did not differ between the BRCA1-related tumours and the controls, which is in line with previous findings (Lynch et al, 1998). In accordance with previous publications concerning E-cadherin expression in BRCA1 carriers (Robson et al, 1998;Armes et al, 1999;Jacquemier et al, 1999), we did not observe different expression levels.…”
Section: Discussionsupporting
confidence: 93%
“…Also, in accordance with other studies (Lakhani et al, 1997;Armes et al, 1998), the BRCA1-related tumours were associated with a lower frequency of in situ carcinoma. The trend towards higher incidence of lymphangio invasion was not found by others (Armes et al, 1998;Robson et al, 1998). Armes et al, reported a significantly lower proportion of tumours showing cyclin D1 over-expression among BRCA1-related tumours (Armes et al, 1999).…”
Section: Discussionmentioning
confidence: 84%
“…We did not have the estrogen-receptor status of the breast cancers in this study; however, it is expected that the majority of BRCA1-associated breast cancers will be ER-negative and that the majority of BRCA2-associated breast cancers will be ER-positive. [4][5][6][7][8][9] These and previous data suggest that tamoxifen is effective in preventing ER-negative second primary cancers. The estrogen-receptor status of the first breast cancer does not influence the actuarial risk of contralateral breast cancer in BRCA1 carriers.…”
Section: Discussionmentioning
confidence: 64%
“…In BRCA1-associated breast cancer, immunohistochemical detection of ErbB2 overexpression is usually found in less than 25% of cases (Johannsson et al, 1997;Robson et al, 1998). In our study, immunohistochemical and Western analysis on primary tumors and cell lines from Brca1 conditional knockout mice demonstrated ErbB2 overexpression.…”
Section: Discussionmentioning
confidence: 74%